Interactive Artificial Intelligence Assistants for Reducing Mathematics Anxiety in Primary Teacher Education - Babicová, Dušana; Jablonský, Tomáš; Tkačik, Štefan; Tkačik jr., Štefan (International Journal of Interactive Mobile Technologies (iJIM), 2026)
Mathematics anxiety represents a significant affective barrier in learning mathematics and may influence both students’ academic performance and their future teaching practice. In teacher education, its reduction is particularly important because negative attitudes toward mathematics may later be transferred to pupils. This study examines the relationship between the perceived pedagogical value (PPV) of an artificial intelligence (AI) assistant and the perceived reduction of mathematics anxiety and explores the mechanism through which AI-supported learning influences students’ affective experience. The study was conducted among students in a primary teacher education program within a course focused on the didactics of arithmetic. Two forms of AI support were implemented: an interactive AI assistant, the Didactic-Arithmetic Coach (DAK), and AI-generated thematic podcasts. Data were analyzed using exploratory factor analysis, correlation, regression, and mediation analysis. The results indicate that the perceived reduction of mathematics anxiety is strongly associated with the academic support provided by the AI assistant, with situational stress reduction acting as a mediating mechanism.